Proizvodna strategija, podprta s teorijo proizvodnih virov - Pandža, Krsto (Strojniški vestnik, 2002)
The idea of using manufacturing as a strategic weapon to achieve competitive advantage is as old as manufacture itself. The content of operations strategy research, however, has greatly changed due to the development of economic environment. The theoretic part of this article presents the resource-based theory and its potential in becoming a leading theoretic concept for operations strategy research. After that a case study is presented whose results add to the development of the resource-based theory. Four successful manufacturing organisations offered the frame for the research. The case study in the manufacturing organisation Primat is presented in detail. The results of the inductive analysis of all four case studies are also presented.
Keywords: organizacija proizvodnje; projektni management; strateški management; strategija